PENGEMBANGAN EKONOMI WILAYAH PERBATASAN INDONESIA–MALAYSIA MELALUI PERDAGANGAN LINTAS BATAS DAN KAWASAN EKONOMI KHUSUS - Nandi Supriyanto; Ela Fatmawati (Adisam Publisher, 2026)
This study examines the economic development of the Indonesia–Malaysia border region through cross-border trade and the development of Special Economic Zones. Border areas are no longer viewed merely as administrative and security boundaries, but as strategic economic spaces with strong potential to support regional connectivity, local economic growth, investment, logistics, and ASEAN economic integration. This research uses a library-based research method, reviewing academic literature, policy documents, institutional reports, and previous studies on border trade, border governance, regional economic cooperation, and Special Economic Zones. The findings show that cross-border trade plays an important role in supporting the livelihoods of border communities, facilitating the movement of goods, strengthening local markets, and improving community welfare. However, its development still faces several challenges, including limited infrastructure, regulatory differences, weak institutional coordination, informal trade practices, and limited capacity of local economic actors. The study also finds that Special Economic Zones can function as strategic instruments to transform border areas into centers of investment, industrial processing, logistics, exports, and value-added production. Therefore, cross-border trade and Special Economic Zones should not be treated as separate policies, but as complementary instruments for border economic development. This study highlights the need for policy harmonization, infrastructure improvement, SME empowerment, digital trade facilitation, and stronger bilateral cooperation between Indonesia and Malaysia. The study concludes that an integrated, collaborative development model is essential to transforming the Indonesia–Malaysia border region into an inclusive, competitive, and sustainable economic growth area.